The first wave of COVID-19 in hospital staff members of a tertiary care hospital in the greater Paris area: A surveillance and risk factors study. (April 2021) - Davido, Benjamin; Gautier, Sylvain; Riom, Isabelle; Landowski, Stephanie; Lawrence, Christine; Thiebaut, Anne; Bessis, Simon; Perronne, Veronique; Mascitti, Helene; Noussair, Latifa; Rancon, Martine Domart; Touraine, Beatrice; et al.
Highlights: Healthcare workers managing COVID-19 were not at higher risk for infection. Using facemasks was the most efficient strategy to avoid in-hospital transmission. Private gatherings outside the hospital was an independent factor for infection. Abstract: Introduction: Understanding how hospital staff members (HSMs), including healthcare workers, acquired severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) during the first wave can guide the control measures in the current second wave in Europe. Methods: From March 5 to May 10, 2020, the Raymond-Poincaré Hospital held a weekday consultation for HSMs for PCR testing. HSMs were requested to complete a questionnaire on their potential exposure to SARS-CoV-2. Results: Of 200 HSMs screened, 70 tested positive for SARS-CoV-2. Ninety-nine HSMs completed the questionnaire of whom 28 tested positive for SARS-CoV-2. In the multivariable analysis, age of ≥44 years (aOR = 5.2, 95% CI [1.4–22.5]) and not systematically using a facemask when caring for a patient (aOR = 13.9, 95% CI [1.8–293.0]) were significantly associated with SARS-CoV-2 infection. Working in a COVID-19-dedicated ward (aOR = 0.7, 95% CI [0.2–3.2]) was not significantly associated with infection. Community-related exposure in and outside the hospital, hospital meetings without facemasks (aOR = 21.3, 95% CI [4.5–143.9]) and private gatherings (aOR = 10, 95% CI [1.3–91.0]) were significantly associated with infection. Conclusions: Our results support the effectiveness of barrier precautions and highlight in-hospital infections not related to patient care and infections related to exposure in the community. Protecting HSMs against COVID-19 is crucial in fighting the second wave of the epidemic.